2021
DOI: 10.1155/2021/5593806
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Significance of Procalcitonin Elevation in Patients over 75 Years Old Admitted for COVID-19 Pneumonia

Abstract: Aim. To investigate the clinical significance of procalcitonin (PCT) elevation on hospital admission for coronavirus disease-19 (COVID-19) and its association with mortality in oldest old patients ( age > 75   years ). Methods. The clinical records of 1074 patients with chest high-resolution computed-tomography (HRCT) positive f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…In a recent study on patients admitted for COVID-19, PCT elevation was associated with several clinical, radiological, and laboratory characteristics of disease severity. However, PCT elevation was strongly associated with hospital mortality only in subjects older than 75 years ( Ticinesi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study on patients admitted for COVID-19, PCT elevation was associated with several clinical, radiological, and laboratory characteristics of disease severity. However, PCT elevation was strongly associated with hospital mortality only in subjects older than 75 years ( Ticinesi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of severe cases of COVID-19 generally involve older subjects, with several comorbidities and relevant pneumonia extension on chest imaging [ 22 , 34 , 35 ]. Age-related frailty represents a consistent risk factor for adverse outcomes in COVID-19 [ 35 , 36 ], also for the increased risk of bacterial superinfection [ 37 ]. Many older subjects included in our study were excluded from remdesivir treatment because their clinical presentation on admission was not compatible with the criteria of prescription [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…As for systemic biomarkers of infection, procalcitonin is a predictor of disease severity ( 31 ), and can be useful to guide antimicrobial stewardship ( 32 , 33 ). Another study found an association between procalcitonin and mortality in COVID-19 patients more than 75 years old ( 34 ). Neutrophil count was also predictive of clinical outcome in hospitalized COVID-19 patients ( 35 ), while the neutrophil-to-lymphocyte ratio was strongly associated with severity and mortality in COVID-19 ( 36 ).…”
Section: Diagnostic and Prognostic Value Of Biomarkersmentioning
confidence: 99%